A Juridical Review of the Building Use Rights Certificate on Land Based on Ownership Claims According to Eigendom Verponding (A Study of Decision Number 227/Pdt.G/2020/Pn Mks) - Bidasari, Anindya; Tuto, Maria Paulina Petrisia (Universitas Negeri Gorontalo, 2024)
Eigendom Verponding is the ownership of land that existed during the Dutch period. The former western land must be converted so that it can be converted into a type of land right based on the UUPA. One of the disputes in the Eigendom Verponding case is contained in Decision Number 227/Pdt.G/2020/PN Mks, where the land object of the dispute is a piece of land with evidence of Eigendom Verponding on land and buildings covering an area of 5000m². The purpose of this study is to find out the settlement of HGB disputes over land based on property claims according to Eigendom Verponding and to find out the judge's considerations in deciding HGB certificate cases on land based on Eigendom Verponding's property claims. This study uses a type of normative juridical research method using the Case Approach and Laws and Regulations. The results of this writing, it was found that the land dispute that occurred between the plaintiff and the defendant where the plaintiff was the owner of Eigendom Verponding which should have been converted into property rights, then sued PT PPI for controlling the land of the object of the dispute with evidence of issuing an HGB certificate, this opens that the defendant has legally controlled the land because it already has permanent legal certainty.